Developing indicators for quality assurance in cytopathology. Catalan Society of Cytopathology. Issue 2 (19th October 2020) - Tresserra, Francisco; Temprana, Jordi; Vasquez, Carem; Lloveras, Belen; Català, Isabel; Tarroch, Xavier; Combalia, Neus; Alameda, Francesc; Bosch, Ramon; Gallardo, Joana; Mancebo, Eva; Fabra, Gemma; et al.
Abstract: Background: Quality control in cytology must be established through reliable and easily measurable indicators. Methods: From the Catalan Society of Cytopathology a group of experts has been established to write a document with 13 indicators that cover the entire cytological process, based on its Cytopathology Quality Guide. It has been elaborated through guides and documents with scientific evidence and DELPHI methodology in order to reach a structured consensus on the opinions of a group of experts. Results: Thirteen indicators, covering all the cytologic process are expressed in worksheets specifying all their characteristics. Conclusion: This document allows the control of all stages of the cytological process.